Molecular and Structural Biomarkers of Inflammation at Two Years After Acute Anterior Cruciate Ligament Injury Do Not Predict Structural Knee Osteoarthritis at Five Years. Issue 2 (4th December 2018) - Roemer, Frank W.; Englund, Martin; Turkiewicz, Aleksandra; Struglics, André; Guermazi, Ali; Lohmander, L. Stefan; Larsson, Staffan; Frobell, Richard
Abstract : Objective: To determine the role of inflammatory biomarkers at 2 years post–anterior cruciate ligament (ACL) injury to predict radiographic knee osteoarthritis (OA) and magnetic resonance imaging (MRI)–defined knee OA at 5 years postinjury, with a secondary aim of estimating the concordance of inflammatory biomarkers assessed by MRI and synovial fluid (SF) analysis. Methods: We studied 113 patients with acute ACL injury. Knee scans using 1.5T MRIs were read for Hoffa‐ and effusion‐synovitis. Biomarkers of inflammation that we assessed included interleukin‐6 (IL‐6), IL‐8, IL‐10, tumor necrosis factor, and interferon‐ɣ in serum and SF, and IL‐12p70 in serum. We defined the outcome as radiographic knee OA (ROA) or MRI‐defined OA (MROA) at 5 years. The area under the receiver operating characteristic curve (AUC), sensitivity, and specificity were evaluated in models that included MRI features only (model 1), inflammation biomarkers only (serum [model 2a] or SF [model 2b]), both MRI features and serum biomarkers (model 3a), or both MRI features and SF (model 3b) biomarkers. Linear regression analysis was used to evaluate the association between MRI features and SF biomarkers. Results: At 5 years postinjury, ROA was present in 26% of the injured knees, and MROA was present in 32%. The AUCs for ROA in each model were 0.44 (95% confidence interval [95% CI] 0.42, 0.47) for model 1, 0.62 (95% CI 0.59, 0.65) for model 2a, 0.53 (95% CI 0.50, 0.56) for model 2b, 0.58 (95% CI 0.55, 0.61) for model 3a, and 0.50 (95% CI 0.46, 0.53) for model 3b. The AUCs for MROA in each model were 0.67 (95% CI 0.64, 0.70) for model 1, 0.49 (95% CI 0.47, 0.52) for model 2a, 0.56 (95% CI 0.52, 0.59) for model 2b, 0.65 (95% CI 0.61, 0.68) for model 3a, and 0.69 (95% CI 0.66, 0.72) for model 3b. The concordance between MRI and SF biomarkers was statistically significant only for effusion‐synovitis and IL‐8. Conclusion: Neither MRI‐detected inflammation nor selected SF/serum inflammation biomarkers at 2 years postinjury predicted ROA or MROA at 5 years postinjury. Concordance between MRI and SF inflammatory biomarkers was weak.